Analisis Kesulitan Siswa Kelas VII SMP Negeri 3 Kartasura Dalam Menyelesaikan Soal Cerita Aritmatika Sosial - Evijayanti, Widya; , Rita Pramujiyanti Khotimah,S.Si, M.Sc (2016)
This research intended to describe the kind difficulties of students in solving social arithmetic story and analyze the factors. This research intended to describe the kind difficulties of students in solving social arithmetic story and analyze the factors. This research qualitative descriptive. Subjects were VIIF grade students of SMP Negeri 3 Kartasura the school year 2015/2016. Data collection methods used tests, interviews, and dokumentasi.Teknik analysis of data through data reduction, data presentation, and conclusion. The results showed that the difficulties experienced by students in solving story arithmetic social: (1) the difficulty in understanding the problem, namely the inability of students in translating a matter that is not able to write what they know and ask. (2) difficulties in the transformation, the inability students in determining the formula to complete social arithmetic problems. (3) difficulties in the settlement process, namely the inability of students to perform arithmetic operations in order to resolve the social arithmetic problems. Factors that lead to students experiencing difficulties are lazy to read about that too long, the difficulty digesting the words in question, the lack of student interest in learning mathematics, student learning is likely to memorize the material, so the concept is not clear, students rarely practice questions, do not understand the arithmetic operation with good, low learning motivation, classroom atmosphere which is less conducive, and learning strategies with the lecture method. Keywords: arithmetic social, about story, difficulty students